In vitro antagonistic activity of trichoderma harzianum against Fusarium sudanense causing seedling blight and seed rot on wheat - Larran, Silvina (2020)
Fusarium sudanense is a novel fungus recently isolated from asymptomatic samples of wheat grains in Argentina. The fungus caused symptoms of seedling blight and seed rot on wheat after artificial inoculations. It is known that the production of mycotoxins by pathogens belonging to the Fusarium genus is harmful to human and animal health. Moreover, the warm and humid conditions that are favorable for growth and mycotoxin production of these species put the Argentinian wheat production area at a high risk of mycotoxin contamination with this novel pathogen. The aim of this work was to evaluate the antagonistic effect of Trichoderma harzianum against F. sudanense under in vitro tests at different environmental conditions. Fungi were screened in dual culture at different water activities (αw) (0.995, 0.98, 0.95, and 0.90) and temperatures (25 and 15 °C). The growth rate of the fungi, interaction types, and dominance index were evaluated. Also, the interaction between T. harzianum and F. sudanense was examined by light and cryo-scanning microscopy. T. harzianum suppressed the growth of F. sudanense at 0.995, 0.98, and 0.95 αw at 25 °C and 0.995 and 0.98 αw at 15 °C. Macroscopic study revealed different interaction types between F. sudanense and T. harzianum on dual culture. Dominance on contact where the colonies of T. harzianum overgrew the pathogen was the most common interaction type determined. The competitive capacity of T. harzianum was diminished by decreasing the temperature and αw. At 0.95 αw and 15 °C, both fungi grew slowly, and interaction type “A” was assigned. Microscopic analysis from the interaction zone of dual cultures revealed an attachment of T. harzianum to the F. sudanense hyphae, penetration with or without formation of appressorium-like structures, coiling, plasmolysis, and a veil formation. According to our results, T. harzianum demonstrated capability to antagonize F. sudanense and could be a promising biocontrol agent.